A decrease in NAD+ contributes to the loss of osteoprogenitors and bone mass with aging - Ha-Neui Kim (Nature Portfolio, 2021)
Abstract Age-related osteoporosis is caused by a deficit in osteoblasts, the cells that secrete bone matrix. The number of osteoblast progenitors also declines with age associated with increased markers of cell senescence. The forkhead box O (FoxO) transcription factors attenuate Wnt/β-catenin signaling and the proliferation of osteoprogenitors, thereby decreasing bone formation. The NAD+-dependent Sirtuin1 (Sirt1) deacetylates FoxOs and β-catenin in osteoblast progenitors and, thereby, increases bone mass. However, it remains unknown whether the Sirt1/FoxO/β-catenin pathway is dysregulated with age in osteoblast progenitors. We found decreased levels of NAD+ in osteoblast progenitor cultures from old mice, associated with increased acetylation of FoxO1 and markers of cell senescence. The NAD+ precursor nicotinamide riboside (NR) abrogated FoxO1 and β-catenin acetylation and several marker of cellular senescence, and increased the osteoblastogenic capacity of cells from old mice. Consistent with these effects, NR administration to C57BL/6 mice counteracted the loss of bone mass with aging. Attenuation of NAD+ levels in osteoprogenitor cultures from young mice inhibited osteoblastogenesis in a FoxO-dependent manner. In addition, mice with decreased NAD+ in cells of the osteoblast lineage lost bone mass at a young age. Together, these findings suggest that the decrease in bone formation with old age is due, at least in part, to a decrease in NAD+ and dysregulated Sirt1/FoxO/β-catenin pathway in osteoblast progenitors. NAD+ repletion, therefore, represents a rational therapeutic approach to skeletal involution.